Suspended conversations : the afterlife of memory in photographic albums - Langford, Martha (McGill-Queen's University Press, 2001)
Introduction: Show and Tell -- The Idea of Album -- The Album as Collection -- Memoirs and Travelogues -- The Idea of Family -- Orality and Photography -- Photographs,1916-945 -- Conclusion: Remembering to Tell -- Appendix 1: A Note on the Photographic Collections at the McCord Museum of Canadian History -- Appendix 2: The Photographic Albums Illustrated in the Text.